Juridical Analysis of Land Arises in the Perspective of Agrarian Reform in Tanjungjaya Village - Rahmatiar, Yuniar; Saripudin, Asep; Mardias, Deni; Anggraeni, Kiki; Sutrisno, Sutrisno; Sanu, Primawan Yunior; Dewi, Yogita (PT. Hafasy Dwi Nawasena, 2024)
This article analyzes the juridical aspects related to the emergence of land in the context of agrarian reform in Tanjungjaya Village. Agrarian reform is an important effort in the redistribution and management of land resources to achieve social and economic justice. This study explores how changes in laws and policies in agrarian reform affect the process of land arising, as well as their implications for land ownership and use rights in the village. Using a juridical analysis approach, this article assesses applicable regulations, administrative procedures, as well as challenges and solutions in the implementation of agrarian reform. The findings show that despite progress in land regulation and redistribution, legal and administrative problems that have not been fully resolved are still an obstacle in the implementation of agrarian reform in Tanjungjaya Village. This research is expected to provide useful insights for policymakers, legal practitioners, and related parties in efforts to improve and adjust agrarian reform policies.